اتجاهات طلبة الجامعة حول الزواج العرفي (دراسة ميدانية أجريت على طلاب جامعة حلب-فرع إدلب ) - نوفل, نوفل أحمد (Latakia University Journal - Arts and Humanities Sciences Series, 2013)
يعتبر الزواج المتكافئ الصحيح المبني على التفاهم والتعاون والمودة،هو الوسيلة الحيوية والطريق الصحيح للحفاظ على المشاعر النبيلة بين الرجل والمرأة، ، والزواج ليس وسيلة إلى الامتزاج البدني الحسي بين الرجل والمرأة فحسب، بل هو الطريق الطبيعي لأصحاب الفطرة السليمة إلى الامتزاج العاطفي والإشباع النفسي والتكامل الشعوري، حيث يعتبر كل من الزوجين لباساً للآخر،يستره ويحميه ويدفئه، قال تعالى:{هن لباس لكم وأنتم لباس لهن}[البقرة:187] وبالنظر لمشاعر الحب التي تتم بين الزوجين فإنها تقوي رابطتهما عن طريق تبادل هذه المشاعر، فالحب أمر فطر الله الناس عليه، وهو رباط قوي بين الرجل وزوجته، فهو السلاح الذي يشقان به طريقهما في الحياة، وهو الذي يساعدهما على تحمل مشاق الحياة ومتاعبها. ومن المشاكل التي غزت مجتمعاتنا العربية، والإسلامية تتجلى ظاهرة الزواج العرفي (أو ما يسمى بالمدني أحياناً) ولكن نتيجة للغزو الفكري للمجتمعات الإسلامية، بدأت تنتشر العلاقات غير الشرعية بين الشباب والفتيات قبل الزواج، تحت شعارات كاذبة مضللة، وبدعوى الحب والتعارف أحياناً، وأن هذا الطريق الصحيح للزواج الناتج، وهذا الأمر يشوبه الكثير من الغموض والضبابية لمن دقق النظر فيما يحدث حولنا، وأنه يجد أن خسائر هذه العلاقات فادحة، وعواقبها وخيمة، وكم من الزيجات بـاءت بالفشل واعتراها كثير من التعثر ،لأنها بدأت بمثل هذه العلاقات ، ولم تعتمد على القوانين الشرعية التي فطر عليها الإنسان . Marriage is considered equal right which was built on mutual understanding, cooperation and affection, it is the vital road Tayeb Tahir to maintain the noble sentiments between men and women, and marriage is not a way to physical sensory mixing between men and women, but it is a natural way to holders of common sense to the emotional mixing, psychological gratification and emotional integration, where each of the spouses is considered a dress for another, conceals, protects and warmth him, he says: {are you as you dress to dress them} [Al-Baqarah: 187] Given the feelings of love, which is made between the couple, it strengthen their connection by sharing these feelings, God has created people with love, which is a strong bond between a man and his wife, it is the weapon that helps them making their way in life, and withstanding the rigors of life and its troubles. One of the problems that have invaded our Arab and Islamic communities is the phenomenon of customary marriages (or so-called Al Madani sometimes), but as a result of the intellectual invasion of Islamic societies, illegitimate relations began to spread among young men and women before marriage, under the slogans of false misleading, and under the pretext of love and dating sometimes, and that this way the right to marry output, and this is tainted by a lot of ambiguity and uncertainty for those who looked more closely to what is happening around us, and it finds that the loss of these relationships is huge, and the consequences dire, how many marriages failed and many stumble, because it began with such relations, and did not rely on legitimate laws people are born with.